2018
DOI: 10.1186/s12891-018-1951-8
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of cervical sagittal parameters in healthy cervical spine adults and patients with cervical disc degeneration

Abstract: BackgroundThe cervical sagittal parameters of the normal population and the impact of disc degeneration on cervical sagittal alignment have not been clearly defined yet. This study is applied to investigate the characteristics and relationships of cervical sagittal parameters in normal adults and patients with cervical disc degeneration.MethodsWe reviewed 50 normal control subjects (normal group, NG) and 50 patients with cervical disc degeneration (degeneration group, DG), who had both cervical MRI and radiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 19 publications
7
42
0
Order By: Relevance
“…In spite of the different abnormal kinematics, this result showed that the CK type is not a risk factor for ANP. In previous studies, approximately 20% asymptomatic individuals showed signs of cervical disc degeneration [28][29][30] . Consistent with these ndings, we also observed signs of disc degeneration in the non-ANP group.…”
Section: Discussionmentioning
confidence: 87%
“…In spite of the different abnormal kinematics, this result showed that the CK type is not a risk factor for ANP. In previous studies, approximately 20% asymptomatic individuals showed signs of cervical disc degeneration [28][29][30] . Consistent with these ndings, we also observed signs of disc degeneration in the non-ANP group.…”
Section: Discussionmentioning
confidence: 87%
“…Nevertheless, multivariate logistic regression showed different CK types was not the risk factor for the ANP, in spite of disc degeneration caused by abnormal kinematics. Previous studies demonstrated almost 20% asymptomatic individuals have cervical disc degeneration [28,29] . Therefore, similar to their study, disc degenration was also found in Non-ANP group.…”
Section: Discussionmentioning
confidence: 99%
“…According to our results, similar results are found in the cervical spine, that is, MC III indicate small sROM and high-level DD grade. However, the patients with MC III have signi cantly smaller CL and C7S than those with MC I, indicating that high-grade DD may be due to the straight cervical spine rather than cervical spine aging [28].…”
Section: II Indicate Unchanged Srom and It Is The Transition Phasementioning
confidence: 94%
“…As the CL, C7S and tDD of the patients with MC I are relatively large (Fig. 4b and 5), the reason why MC I is always accompanied by high-grade DD can be explained by cervical spine aging, because the increase in CL and C7S is considered to be a compensatory change in the aging process of the cervical spine [28].…”
Section: I Indicate Small Srom and Advanced Dd Gradementioning
confidence: 98%